Pengaruh Rebusan Daun Sirsak dalam Menurunkan Tingkat Nyeri terhadap Gastritis - Cut Mah Bengi Aminesta; Syukriadi Syukriadi; Mansuriza Mansuriza; Maidayani Maidayani; Muhammad Rizki (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Gastritis usually occurs in people with irregular eating patterns and consuming foods that stimulate stomach acid production. Inflammation of the gastric mucosa or lining can be caused by various factors. The purpose of this study was to determine the effect of soursop leaf decoction on reducing gastritis pain. This research used a quasi-experimental design with a one-group pretest-posttest approach. The sample size was 15 people, using accidental sampling. This study was conducted from June 12 to 18, 2025. Data were obtained through observation sheets using the Numeric Rating Scale (NRS). Normality was tested using the Shapiro-Wilk test, and data analysis used the paired t-test. The results showed that before the soursop leaf decoction, the average pain score for respondents was 0.074, while after the decoction, the pain score decreased to 0.151, a decrease of 0.007 with a P-value of 0.001 (<0.05). Conclusion: The soursop leaf decoction is effective in reducing gastritis pain. Respondents are encouraged to regularly consume the soursop leaf decoction when experiencing pain, and it can serve as a reference for future research using different variables.